1989
DOI: 10.1177/0148607189013003246
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Fat Emulsion (Intralipid) Delays Gastric Emptying, but Does Not Cause Gastroesophageal Reflux in Healthy Volunteers

Abstract: The impact of overnight intravenous lipid emulsion (ILE) infusion on upper gastrointestinal tract physiology was assessed in 10 healthy volunteers. No changes in lower esophageal sphincter pressure (before infusion: 28 +/- 4 mm Hg; after infusion 20.5 +/- 3; p:NS), plasma concentrations of gastrointestinal hormones (gastrin: preprandial before/after lipids: 14 +/- 2.1/13 +/- 1.4 pM; postprandial before/after lipids: 28 +/- 2.7/30 +/- 3.4 pM, CCK: preprandial before/after lipids: 69 +/- 10/64 +/- 10 pM; postpra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 11 publications
(2 reference statements)
0
6
0
1
Order By: Relevance
“…The current data suggest that increasing the quantity of co‐administered lipid (relative to drug) has the capacity to enhance oral bioavailability to a certain point, but that increases beyond 250 mg (∼750 mg/kg) provide little practical benefit and serve only to extend T max . The latter may reflect a reduction in gastric emptying due to the presence of higher quantities of lipid43,44 or a reduction in the efficiency of lipid digestion and processing.…”
Section: Resultsmentioning
confidence: 99%
“…The current data suggest that increasing the quantity of co‐administered lipid (relative to drug) has the capacity to enhance oral bioavailability to a certain point, but that increases beyond 250 mg (∼750 mg/kg) provide little practical benefit and serve only to extend T max . The latter may reflect a reduction in gastric emptying due to the presence of higher quantities of lipid43,44 or a reduction in the efficiency of lipid digestion and processing.…”
Section: Resultsmentioning
confidence: 99%
“…Casaubon et al 16 reported that IV lipid infusion caused gastric emptying delay, but they did not study the effect on the interdigestive motor activities in the stomach. Guedon et al 17 demonstrated that IV lipid infusion with a high infusion rate (5 hours of 100 mL/h infusion) decreased occurrences of phase III in the jejunum.…”
Section: Discussionmentioning
confidence: 99%
“…La administración intravenosa de emulsiones de grasa también retrasa el vaciamiento gástrico y puede contribuir a este fenómeno. 149,150 Trastornos de la alimentación. La anorexia nerviosa es una afección psiquiátrica que ocurre principalmente en mujeres adolescentes y adultas jóvenes caracterizado por una deformación de la imagen corporal y temor a la obesidad con dietas compulsivas e inanición autoimpuesta para conservar un peso corporal notablemente bajo.…”
Section: Trastornos No Gastrointestinales Que Se Acompañan De Retrasounclassified